A BIM for safety Framework Involving Automated Rule Checking, Visualization and Training - Adeeb Sidani (2021)
The construction industry bears a lot of casualties and accidents more than other high-risk industries annually. Thus, to have a practical site inspection, monitoring, and training, the AECO (Architecture, Engineering, Construction, and operation) is gradually integrating new digital technologies such as building information modelling (BIM), automatic rule checking, Augmented and Virtual Reality (AR/VR). The current research objective is to provide a general framework of a BIM-based safety system to improve the safety status in the construction field. The system aims to offer Safety planning, Visualization, safety management, training, automated rule checking, monitoring and inspection. A BIM for Safety verification system is proposed, based on a fully automated approach, adopting Automated rule checking, and a manual approach adopting Virtual and Augmented Reality (AR/VR). These two systems will be a part of a BIM for Safety General Framework, which covers the construction project lifecycle with all the involved stakeholders and international standards. The BIM-based technologies can help with safety prevention, inspection, monitoring, and training from the design stage to the operation and management. The integration of these tools in a standardised manner could ease the adoption of the tools, following EN ISO 19650‑1 and PAS 1192-6:2018, giving the owner better awareness and control over the safety aspects of the project, identifying specific tasks for each stakeholder, and involving health and safety measures from the beginning of the project. Some limitations are found in implementing new tools since every tool represents a standalone, each tool covers a specific field only, the digital tools are not involved in the standards and regulations, workers and safety professionals lack the experience of using such tools, low demand from the owners, incompatibility of software and data format exchange, especially between different appointed parties, and the time spent preparing the BIM model.